PELAYANAN KTP ELEKTRONIK DI MASA PANDEMI COVID-19 PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BAUBAU - Ahmad Farouq Mulku Zahari; Anis Ribcalia Septiana; Taslim Fait (Journal Publicuho, 2021)
The purpose of this research is to find out how the service for making electronic ID card during the Covid-19 pandemic at the Department of Population and Civil Registration of Baubau City, as well as what are the inhibiting and supporting factors in providing services to the community. This research uses a descriptive qualitative approach through literature studies. The results show that the Department of Population and Civil Registration of Baubau City has implemented public services according to service standards in making electronic ID card, where services are carried out online using the WhatsApp (WA) application via an Android phone, the public is also free of charge in the manufacturing process, providing facilities and adequate infrastructure in accordance with the Covid-19 health protocol, and placing competent officer to facilitate service delivery. The results of this study also reveal the factors that affect the service of making electronic ID cards at the Department of Population and Civil Registration of Baubau City, during the Covid-19 pandemic, namely: supporting factor where the tools available in providing services are adequate and the human resources competent in their field. Even though there are several technical obstacles, especially from the internet network, not all people have an Android phone and understand the mechanism of online service.